2011
DOI: 10.1182/blood-2010-02-270561
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial LSP1 is involved in endothelial dome formation, minimizing vascular permeability changes during neutrophil transmigration in vivo

Abstract: The endothelium actively participates in neutrophil migration out of the vasculature via dynamic, cytoskeleton-dependent rearrangements leading to the formation of transmigratory cups in vitro, and to domes that completely surround the leukocyte in vivo. Leukocyte-specific protein 1 (LSP1), an F-actin-binding protein recently shown to be in the endothelium, is critical for effective transmigration, although the mechanism has remained elusive. Herein we show that endothelial LSP1 is expressed in the nucleus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 52 publications
4
77
1
Order By: Relevance
“…transmigratory cups, apical cups, dome structures, ICAM-1-enriched contact areas, or actin dynamic structures. 14,[67][68][69][70][71] The names were based on the hypothesized function or morphology of these structures. Work of Carman and coworkers showed that these structures, that formed both during para-and transcellular diapedesis (Fig.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 99%
“…transmigratory cups, apical cups, dome structures, ICAM-1-enriched contact areas, or actin dynamic structures. 14,[67][68][69][70][71] The names were based on the hypothesized function or morphology of these structures. Work of Carman and coworkers showed that these structures, that formed both during para-and transcellular diapedesis (Fig.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 99%
“…Moreover, transmigrating cups around neutrophils has been shown to be a mechanism for the maintenance rather than disruption of barrier function. 64 These discrepancies will need to be resolved in future studies.…”
Section: Cytoadherencementioning
confidence: 99%
“…Using in vivo spinning disk or multi-photon confocal microscopy, profound anatomical changes of the endothelium that facilitated leukocyte extravasation without compromising vascular barrier integrity were observed Petri B. et al, 2011). Docking cup-like structures were formed by endothelial cells (endothelial projections) at the base of the transmigrating neutrophil, which has also been described for T-lymphocytes in vitro (Carman C. V., Springer T. A., 2004).…”
Section: Diapedesis: Trans-and Paracellular Routesmentioning
confidence: 99%
“…The endothelial projections extended towards the top of the neutrophil and eventually formed a dome that surrounded the entire neutrophil, prior to basolateral opening and neutrophil migration further into tissue. If the dome formations were prevented, neutrophil transmigration was delayed (Petri B. et al, 2011), further implicating an active role of endothelium during leukocyte diapedesis, while maintaining the barrier function and vascular permeability.…”
Section: Diapedesis: Trans-and Paracellular Routesmentioning
confidence: 99%